Climate change adaptation networks for small and medium-sized cities - Simone Häußler; Wolfgang Haupt (SN Social Sciences, 2021)
Cities are particularly vulnerable to the impacts of climate change. Many larger cities have identified the potential impacts of different climate change adaptation scenarios. However, their smaller and medium-sized counterparts are often not able to address climate risks effectively due to a lack of necessary resources. Since a large number of cities worldwide are indeed small and medium-sized, this lack of preparedness represents a crucial weakness in global response systems. A promising approach to tackling this issue is to establish regional municipal networks. Yet, how might a regional network for small and medium-sized cities be systematically designed and further developed? Focussing on the German federal state of Baden-Wuerttemberg, we have explored this question by applying a participatory action research approach. As part of our research, we established a regional network framework for small and medium-sized cities. The framework supports small and medium-sized cities in identifying key regional actors, while taking local and regional contextual factors into account. Based on our findings, we suggest that other small and medium sized cities follow these steps: develop the knowledge base; build the network; and transfer and consolidate knowledge.
Keywords: 300; City networks; Climate change adaptation; Key actors; Knowledge transfer; Regional network framework; Participatory action research